Body / image in the discourse of advertising through semiotics Bartlett (Roland Bart) - Mansour, Awatif (Journal of Humanities & Social Sciences, 2017)
The specificity of advertising speech consists in settling a fixed mark in the era of globalization. It is based on a duality that inter Wins the body in general, and the body of the finale media Marketing. Starting from the semiotics approach of Roland Barth. We will address to study the image of the female body in the advertising speech and its influential relationship between the producer and the consumer by interpreting the fixed and mobile images and denotes as connotations and messages and energies suggestive and a built-in graphical and unannounced. In general, the body has become on effective feature on the receiver in the world of publicity. As it has become a consume ring product. So the latter turns, in the advertising speech from an image to a mark and icon with interpretive load. It also turns to open several readings where lies the strength of reporting and the elements of semantic, suggestive and effectiveness in influencing the receivers. Based on all this we will try to interpret the female body in the advertising speech from semiotics Barth perspective by focusing on its functions and analysis with an attempt to provide practical models through its presence in pictures such as television, cinema, media, Walls... therefore and artistic elements. So, advertising is a media art based on the visible indicators establishing the relationship between the receiver and the consumers We will work with Roland Barth in an interactive way to infer the image of the body in the advertising speech as a semeologie field and the dismantling of his grades.
Keywords: semiotic approach; advertising and marketing discourse; female body/image; seduction and excitement; message and addressee